When is the right time?. (20th January 2018) - Reid, Jacky; Nolan, Andrea; Scott, Marian
Abstract : Veterinary medicine is veering further towards prolongation of life at all costs, without the safeguard of being able to robustly measure quality of life. Jacky Reid, Andrea Nolan and Marian Scott discuss major steps forward in the ability to measure changes in health‐related quality of life.